Yes, we CANZ: initial compliance and lessons learned from regulating vessel biofouling management in California and New Zealand - Scianni, Chris; Lubarsky, Katie; Ceballos-Osuna, Lina; Bates, Tracey (Management of biological invasions, 2021)
In 2017 and 2018, California and New Zealand introduced new regulatory regimes for the maritime shipping industry by implementing and enforcing regulations for biofouling management. Both sets of regulations reflect the principles of the International Maritime Organization’s Biofouling Guidelines and are designed to encourage proactive biofouling management to reduce the likelihood of nonindigenous species introductions. During the first year of enforcement, maritime shipping vessels that were subject to the respective regulations made similar numbers of arrivals at California (2,515) and New Zealand (2,556) ports. California and New Zealand regulators also conducted similar numbers of biofouling inspections during this time: 505 in California and 498 in New Zealand. Most instances of noncompliance in both jurisdictions were a result of incomplete understanding of these new regulations, however provisions to provide flexibility and education ensured the maritime shipping industry had opportunities to learn about the requirements, improve compliance, and reduce learning curves. An important lesson learned for both jurisdictions was the importance of extensive and targeted outreach to the various stakeholder groups that play a role in achieving compliance and effective risk reduction. The lessons learned and noncompliance trends identified during the first year of inspections in California and New Zealand provide valuable insights for consideration in light of the current review of the IMO Biofouling Guidelines and moves to develop biofouling requirements in other jurisdictions.